Fibrinolysis and Fibrinogen Breakdown Products (Antithrombin VI) in Renal Venous Blood (RVB) in Dog - Worowski, K; Niewiarowski, S; Prokopowicz, J (Thrombosis and Haemostasis, 1964)
The authors investigated fibrinolytic system of renal venous blood (RVB) peripheral venous blood (PVB) in normal dogs and in those with kidney injury produced by mercury chloride. An increase of fibrinolytic activity as well as a decrease of the level of plasminogen and fibrinogen were found in RVB plasma of normal dogs. An inhibition of the fibrinolytic activity was found in intoxicated dogs in both RVB and PVB plasmas, followed by an increase of plasminogen and fibrinogen levels. The occurence of fibrinogen breakdown products, antithrombin VI, was demonstrated in RVB plasma of normal dogs. It does not appear in RVB plasma of intoxicated dogs.On the basis of experimental results an important role of urokinase, secreted by the kidney into the general circulation is suggested as regards the maintenance of the coagulation and fibrinolysis balance in the organism as well as in the fibrinogen and plasminogen catabolism.It has been also concluded that the antithrombin VI, formed in the kidney circulation is a natural inhibitor of blood coagulation appearing in physiological conditions.